2011
DOI: 10.1007/s10764-011-9499-6
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Chimpanzees (Pan troglodytes troglodytes) and Gorillas (Gorilla gorilla gorilla) in Loango National Park, Gabon: Dietary Composition, Seasonality, and Intersite Comparisons

Abstract: Dietary overlap of sympatric apes is complex and understudied, but its examination is essential to further our understanding of species distribution, abundance, and community ecology. Over 3 yr we studied food availability and dietary composition of central chimpanzees (Pan troglodytes troglodytes) and western gorillas (Gorilla gorilla gorilla) in Loango National Park, Gabon. We predicted that living in a habitat dominated by mature forest with sparse terrestrial herbaceous vegetation would lead to an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 44 publications
8
149
3
Order By: Relevance
“…Fecal analysis at both sites suggested that chimpanzees were more frugivorous than gorillas (Stanford and Nkurunungi, 2003;Head et al, 2011). While we detected this niche differentiation in 13 C, the patterns in 15 N as well as the overall isotopic variation in hair were not consistent.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…Fecal analysis at both sites suggested that chimpanzees were more frugivorous than gorillas (Stanford and Nkurunungi, 2003;Head et al, 2011). While we detected this niche differentiation in 13 C, the patterns in 15 N as well as the overall isotopic variation in hair were not consistent.…”
contrasting
confidence: 58%
“…When interpreting the 13 C values of unhabituated chimpanzees, we additionally related these data to those of gorillas which are generally regarded as more folivorous than chimpanzees (e.g., Head et al, 2011 and references therein). A more folivorous diet in gorillas is also supported by isotopic evidence (Macho and Lee-Thorp, 2014;Oelze et al, 2014).…”
Section: Analyses Of Vegetation Baselinesmentioning
confidence: 99%
“…All newly characterized SIVgor sequences fall within the previously identified radiation of SIVgor strains, indicating that SIVgor has emerged only once. Chimpanzees and gorillas have overlapping habitats and often feed in the same fruit trees (33)(34)(35). Sharing the same habitat leads to direct and indirect contacts, which have resulted in the cross-species transmission of other pathogens, such as the agents of anthrax, Ebola, and hepatitis B (15,(36)(37)(38).…”
Section: Sivgor Resulted From a Single Introduction Of Sivcpz From Symentioning
confidence: 99%
“…These two closely related species have significant overlap in their dietary pattern and resource use, but differ significantly in their use of fallback foods and food-harvesting strategies. Whereas both species appear to focus on fruit as their primary, preferred food, gorillas are willing to consume herbaceous vegetation when their preferred food item is unavailable; chimpanzees, on the other hand, broaden their home range to harvest their preferred food and do not use herbaceous vegetation as their fallback food (93)(94)(95)(96). It is possible that, analogous to modern chimpanzees and gorillas, one of the two Australopithecus species at Woranso-Mille had greater ecological niche breadth, or they may have specialized in different fallback foods during times of preferred food scarcity, while sharing the same resources when preferred food items are abundant.…”
Section: Pliocene Hominin Diversity Sympatry and The Question Of Nimentioning
confidence: 99%